THE INFLUENCE OF CELEBRITY ENDORSEMENT AND CONTENT MARKETING ON PURCHASE INTENTION OF SKINTIFIC PRODUCTS AT TIKTOK SHOP - Lombogia, Stacia Clearesta; Tumbuan, Willem J. F. Alfa; Saerang, Regina T. (Universitas Sam Ratulangi, 2024)
The primary objectives of this research are threefold: firstly, to know the Influence of Celebrity Endorsement on Purchase Intention of Skintific Products at Tiktok Shop; secondly, to know the Influence of Content Marketing on Purchase Intention of Skintific Products at Tiktok Shop; thirdly to know the Influence of Celebrity Endorsement and Content Marketing on Purchase Intention of Skintific Products at Tiktok Shop;. The research adopts a quantitative approach, involving the number of sample of 100 respondents of Gen Z Manado. Multiple linear regression analysis, utilizing SPSS Version 20 as the analytical tool, demonstrates that Celebrity Endorsement and Content Marketing significantly Influence Purchase Intention. Keywords: Celebrity Endorsement, Content Marketing, Purchase Intention